2015
DOI: 10.1186/s12890-015-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidental gastrointestinal 18F-Fluorodeoxyglucose uptake associated with lung cancer

Abstract: BackgroundF-Fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) is increasingly used for the initial staging and restaging of lung cancer. Incidental gastrointestinal findings are often observed on 18F-FDG PET/CT. The objective of this study was to assess incidental 18F-FDG uptake by the gastrointestinal tract (GIT) in patients with lung cancer.MethodsTwo hundred thirty consecutive 18F-FDG PET/CT examinations performed for lung cancer over a 3-year period were retrospectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(29 reference statements)
0
0
1
Order By: Relevance
“…Second malignant or premalignant lesions were confirmed in all but one patient who showed PET/CT with focal uptake: the remaining patient with a focal FDG uptake had a colonic metastasis from pancreatic cancer confirmed by pathologic examination. The number of incidental findings in our study appears higher than that reported by other authors [ 10 , 11 ] but much greater incidence (more than 20%) has been reported for other types of primary neoplasms [ 9 , 12 ].…”
Section: Discussioncontrasting
confidence: 84%
“…Second malignant or premalignant lesions were confirmed in all but one patient who showed PET/CT with focal uptake: the remaining patient with a focal FDG uptake had a colonic metastasis from pancreatic cancer confirmed by pathologic examination. The number of incidental findings in our study appears higher than that reported by other authors [ 10 , 11 ] but much greater incidence (more than 20%) has been reported for other types of primary neoplasms [ 9 , 12 ].…”
Section: Discussioncontrasting
confidence: 84%